Reagentless Amperometric Glucose Biosensors: Ferrocene-Tethering and Copolymerization - Altun, Ayhan; Apetrei, Roxana-Mihaela; Camurlu, Pinar (Electrochemical Soc Inc, 2020)
Ferrocene-substituted 2,5-di(thienyl)pyrrole (SNS-Fc) was electrochemically polymerized in the presence and absence of 3,4-ethylenedioxythiophene (EDOT) and utilized for biosensing upon immobilization of glucose oxidase (GOD) through cross-linking. The two biosensors, homopolymer P(SNS-Fc) and copolymer-based P(SNS-Fc-co-EDOT) were evaluated by comparison in terms of analytical performance. Due to the conducting-redox active nature of the films, the study was able to consider the developed sensors both as "first generation," monitoring H(2)O(2)oxidation and as "second generation," using the optimum potential for ferrocene oxidation. The difference in performance at these two working potentials served as assessment of the influence of ferrocene moiety within the conducting film. In the scope of further improvement, carbon nanotubes (MWCNTs) were incorporated in both type systems. This improved the detection efficiency leading to extension of linear range up to 1.5 mM with sensitivity up to 23.12 mu A mM(-1)cm(-2)and detection limits as low as 0.43 mu M. The proposed biosensors showed little to no interference to other saccharides and accurate recovery in real sample analysis, especially when glucose detection was based on mediated electron transfer. Thus, the association of ferrocene, poly 2,5-di(thienyl)pyrroles and CNTs is highly efficient in the development of sensitive "reagentless" biosensor systems.
APETREI, ROXANA-MIHAELA/0000-0002-5669-8968; ALTUN, AYHAN/0000-0002-0931-4693
Keywords: Sensors; Electroanalytical Electrochemistry; Bioelectrochemistry